Балансуючий ринок електроенергії України та його математична модель - Кириленко, О.В.; Блінов, І.В.; Парус, Є.В. (Технічна електродинаміка, 2011)
In the article mathematical model is given and the features of holding of balancing electricity market are defined. The mathematical method of active power balance optimization in auction for balancing electricity market is defined. The development method of active power balance optimization in power system is based on mathematical apparatus of the loss coefficients. The method allowed the structure of generation power with a glance of specific cost of power generation and transmission losses without simulation and optimization of power flow in power system.